Prevalence, triggers and presentation of migraine among the college and university students: review of the available literature - Quratulain Javaid (Journal of the Pakistan Medical Association, 2021)
Migraine is one of the types of headache, associated with causing disability. It is considered as a third main cause of disability among the individuals lesser than 50 years. Environment around us does play an essential role in triggering the symptoms of migraine. The painful episodes can be prevented by adopting certain lifestyle influences. It affects daily life activities of the students. Research articles were analyzed by the help of three databases; Google, Google Scholar and PUBMED database from 2015 to 2020. Migraine pain is prevalent at different levels among the college and university students, being more common in the females as compared to males. Identifying triggers is an essential feature in identifying and thus preventing the severity of migraine. As the disease effect quality of students’ life, that is why it is essential to create more awareness so that students can approach physicians and undisturbed. Continuous...